Catalogue of the (Fred) Olsen Collection (Guilford, Conn.) of Persian Pottery and Works of Art. Sotheby Sales Catalogue - Anonymus, A. (1964)
Date of Sale: June 8, 1964; spez. Nos. 1-21 (16, 17, 21 ill.) Luristan-Bronzen und Nos. 24-43 (24 und 37 ill.) Keramik aus Tepeh Sialk und Тереh Giyan.